The Complex Role of Thrombin in Cancer and Metastasis: Focus on Interactions with the Immune System - Aleksandrowicz, Karolina; Hempel, Dominika; Polityńska, Barbara; Wojtukiewicz, Anna M.; Honn, Kenneth V.; Tang, Dean G.; Wojtukiewicz, Marek Z. (Seminars in Thrombosis and Hemostasis, 2023)
Thrombin, a pleiotropic enzyme involved in coagulation, plays a crucial role in both procoagulant and anticoagulant pathways. Thrombin converts fibrinogen into fibrin, initiates platelet activation, and promotes clot formation. Thrombin also activates anticoagulant pathways, indirectly inhibiting factors involved in coagulation. Tissue factor triggers thrombin generation, and the overexpression of thrombin in various cancers suggests that it is involved in tumor growth, angiogenesis, and metastasis. Increased thrombin generation has been observed in cancer patients, especially those with metastases. Thrombin exerts its effects through protease-activated receptors (PARs), particularly PAR-1 and PAR-2, which are involved in cancer progression, angiogenesis, and immunological responses. Thrombin-mediated signaling promotes angiogenesis by activating endothelial cells and platelets, thereby releasing proangiogenic factors. These functions of thrombin are well recognized and have been widely described. However, in recent years, intriguing new findings concerning the association between thrombin activity and cancer development have come to light, which justifies a review of this research. In particular, there is evidence that thrombin-mediated events interact with the immune system, and may regulate its response to tumor growth. It is also worth reevaluating the impact of thrombin on thrombocytes in conjunction with its multifaceted influence on tumor progression. Understanding the role of thrombin/PAR-mediated signaling in cancer and immunological responses is crucial, particularly in the context of developing immunotherapies. In this systematic review, we focus on the impact of the thrombin-related immune system response on cancer progression.
Keywords: thrombin; neoplasm; metastasis; immune system; platelets; protease-activated receptors; neutrophil extracellular traps